New extension of Burr type X distribution properties with application - Abdullah Khaleel, Mundher; Ibrahim, Noor Akma; Shitan, Mahendran; Merovci, Faton (Elsevier, 2018)
We introduce a new distribution named Exponentiated Generalized Burr type X (EGBX) distribution with four parameters. This new model can be expressed as a mixture of Burr type X (BX) distribution with different parameters. Several sub models are investigated and also some important structure properties of new model are derived including the quantile function, limit behavior, the rth moment, the moment-generating function, Rényi entropy, and order statistics. We estimate the parameters using the maximum likelihood estimation. Finally, simulation study is carried at under varying sample size to assess the performance of this model, the flexibility of EGBX distribution is illustrated by using real data set.